Mycosis fungoides-type cutaneous T-cell lymphoma (MF-CTCL) epidemiology and treatment pathway in Spain: new insights for an accurate description - Paolo D'Agostino; Alan Kent; Eric Sharp; Fabian Schmidt; Marco Turini (BioExcel Publishing Ltd, 2020)
Background: Mycosis fungoides-type cutaneous T-cell lymphoma (MF-CTCL) is a rare lymphoma localized in the skin. Due to its indolent nature and similarity to other skin conditions, diagnosis is often delayed or incorrect. Consequently, accurate calculations of incidence and prevalence are difficult to make. The treatment pathway taken by MF-CTCL patients can differ depending upon local healthcare systems, clinical policies and guidelines. Aims: This study aims to (1) provide an estimate for the prevalence of treated MF-CTCL patients in Spain, (2) describe the Spanish patient treatment pathways for MF-CTCL, including quantification of the distribution of patients between primary, secondary and tertiary care institutions, and (3) investigate and quantify the treatment preferences of physicians. Methodology: This study employed primary market research methodologies to facilitate the collection of patient numbers and treatment practices from healthcare professionals (HCPs) and patients. Limitations: Poor diagnosis of MF-CTCL may mean that actual prevalence levels in the broader population are higher than those estimated by this analysis of treated patients. This study was reliant upon accurate reporting by HCPs of patient numbers and their personal treatment practices. The rarity of the condition means the patient sample size is relatively small and limits possible accuracy of the quantitative analyses of patientderived data, although this is supplemented by HCP-derived data in the analysis. Findings: Around 75% of MF-CTCL patients in Spain report that the initial diagnosis by their general practitioner is incorrect. This is usually due to underestimation of severity or type of skin disease. Once they have been correctly diagnosed (usually by a dermatologist) in secondary care, the management of MF-CTCL is led by dermatologists. In 39% of patients, shared care teams are also involved in patient management. Following diagnosis, the majority of patient management is conducted by secondary or tertiary care centers. Conclusions: Incidence rates have increased in recent years, and possible reasons for this include improving levels of diagnosis. Survival in MF-CTCL has also increased over the last few decades. This trend appears to be reflected in the prevalence reported in this study, which is higher than suggested by some other estimates. However, it is still likely that there are further undiagnosed MF-CTCL patients in Spain due to the challenges of diagnosis at the primary care level.